A New Age of SAR: How Can Commercial Smallsat Constellations Contribute to NASA's Surface Deformation and Change Mission? - Stacey A. Huang; Batuhan Osmanoğlu; Bernd Scheuchl; Shadi Oveisgharan; Jeanne M. Sauber; MinJeong Jo; Ala Khazendar; Ekaterina Tymofyeyeva; Betsy Wusk; Arif Albayrak (Earth and Space Science, 2025)
Abstract In response to the 2017 Decadal Survey, NASA conducted a five‐year study on the Surface Deformation and Change (SDC) designated observable to study potential mission concepts. As part of the SDC mission study, the Commercial Synthetic Aperture Radar (ComSAR) subgroup was tasked with evaluating the current landscape of the SAR and interferometric SAR (InSAR) industry to assess whether NASA could leverage commercial smallsat products to meet the needs of the SDC science mission. The assessment found that although the commercial SAR industry is growing rapidly, off‐the‐shelf products can currently only make a small—albeit distinct—contribution to SDC mission goals. This gap is due to different design goals between current commercial systems (which prioritize targeted high‐resolution, non‐interferometric observations at short wavelengths with a daily or faster revisit) and a future SDC architecture (which focuses on broad, moderate‐resolution, and interferometric observations at long wavelengths). Even by 2030, planned commercial constellations are expected to only cover ∼65% of the area needed to match NISAR coverage. Still, high‐resolution and rapid‐repeat capabilities can augment scientific findings from a future SDC mission, as demonstrated by recent contributions from commercial data to applied sciences, cryosphere, and volcanology. Future innovations on smallsat constellation concepts could further contribute to SDC science and applications. Although current constellation designs are not fully able to satisfy desired SDC science capabilities, initial positive feedback to a request for information indicates a potential future path for a customized SDC commercial architecture; more studies will be needed to determine the feasibility of these approaches.